New insights into the mechanism of nickel superoxide degradation from studies of model peptides. Issue 1 (December 2017) - Tietze, Daniel; Sartorius, Jana; Koley Seth, Banabithi; Herr, Kevin; Heimer, Pascal; Imhof, Diana; Mollenhauer, Doreen; Buntkowsky, Gerd
Abstract A series of small, catalytically active metallopeptides, which were derived from the nickel superoxide dismutase (NiSOD) active site were employed to study the mechanism of superoxide degradation especially focusing on the role of the axial imidazole ligand. In the literature, there are contradicting propositions about the catalytic importance of the N-terminal histidine. Therefore, we studied the stability and activity of a set of eight NiSOD model peptides, which represent the major model systems discussed in the literature to date, yet differing in their length and their Ni-coordination. UV-Vis-coupled stopped-flow kinetic measurements and mass spectrometry analysis unveiled their high oxidation sensitivity in the presence of oxygen and superoxide resulting into a much faster Ni(II)-peptide degradation for the amine/amide Ni(II) coordination than for the catalytically inactive bis-amidate Ni(II) coordination. With respect to these results we determined the catalytic activities for all NiSOD mimics studied herein, which turned out to be in almost the same range of about 2 × 106 M−1 s−1 . From these experiments, we concluded that the amine/amide Ni(II) coordination is clearly the key factor for catalytic activity. Finally, we were able to clarify the role of the N-terminal histidine and to resolve the contradictory literature propositions, reported in previous studies.